The Effect of Loan to Deposit Ratio and Non-Performing Loans on Stock Prices with Return on Assets as an Intervening Variable at Regional Development Banks - Putri, Hana Tamara; Amali, Muhammad; Masyhuri, Ade (Ekonomis: Journal of Economics and Business, 2024)
This research analyzes the effect of the loan to deposit ratio (LDR) and non-performing loan (NPL) on return on assets (ROA). Stock price, loan to deposit ratio (LDR), and non-performing loan (NPL) to stock price with return on assets (ROA) as the intervening variable. They are using quantitative secondary data from the annual financial report of the regional development bank listed on the Indonesia stock exchange in 2016-2020, analysing with path analysis. The results indicate that LDR has no significant effect on stock prices, NPL has no considerable effect on stock prices, LDR has no significant impact on ROA, NPL has no significant impact on ROA, and ROA has a positive and significant impact on stock prices.